The Influence of Brand Image, Religiosity and Halal Labels on Purchasing Decisions of Packaged Food Products: Case Study of IAIN Pekalongan Students - Fitriana Nur Rohmah (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
Packaged food is food that can be found anywhere at this time. The soaring population growth rate which continues to increase, has an impact on the development of the food industry in Indonesia. Therefore, many companies compete with each other to meet the needs of consumers, by continuously improving quality and innovation in each of their products. The purpose of this study is to determine the effect of brand image, religiosity and halal labels on purchasing decisions for packaged food products (a case study of IAIN Pekalongan students) partially and simultaneously. This study uses a quantitative approach to causal investigation. Data were gathered from primary and secondary sources, although the information for this study came through questionnaires. The stripping population is IAIN Pekalongan students for the 2020 academic year. The sampling technique used is a probability sample using a simple random sampling technique with a sample size of 100 respondents. Methods of data analysis from this study using the classical assumption test, multiple linear regression test and hypothesis testing. The results showed that partially and simultaneously there was an influence between brand image, religiosity and halal labels on the decision to purchase packaged food products for consumers of Muslim students at IAIN Pekalongan. The influence of brand image on the decision to purchase packaged food products is 0.002 <0.05 or tcount on the brand image variable is 3.161 > 1.983. The influence of religiosity on purchasing decisions for packaged food products is 0.000 <0.05 and tcount on the religiosity variable is 3.621 > 1.983. The influence of the halal label on the decision to purchase packaged food products is 0.000 <0.05 and tcount on the halal label variable is 5.574 > 1.983. The influence of brand image, religiosity and halal label on purchasing decisions of packaged food products is 0.000 <0.05 and Fcount is 53.983 > Ftable 2.70.